Rational Design of New Dihydrobenzooxophosphole-Based Lewis Base Organocatalysts - Qu, Bo; Samankumara, Lalith P.; Saha, Anjan; Schumer, Mac G.; Han, Zhengxu S.; Haddad, Nizar; Busacca, Carl A.; Yee, Nathan K.; Kozlowski, Marisa C.; Song, Jinghua J.; Senanayake, Chris H. (Synlett, 2020)
A series of new dihydrobenzooxophosphole-based Lewis base organocatalysts were designed and synthesized. They are shown to be effective in trichlorosilane-mediated stereoselective conjugate reductions of C=C bonds. DFT calculations reveal that the strong hydrogen bonds between the amide linker and the chloride on silicon in the transition state contribute to the high reactivity of the catalyst.
Keywords: chiral Lewis base; organocatalyst; enone reduction; hydrogen bonds